Problematika sistem pendidikan di Indonesia dan solusi pemecahannya - Mahfudhoh, Aini (Maliki Interdisciplinary Journal, 2024)
This article aims to examine the current education system in Indonesia with several problems faced and solutions to deal with them. Changes in the implementation of education in Indonesia require the performance and support of all parties, both society and government. Advanced and quality education reflects that the country has succeeded in developing the country and its human resources. This research uses a descriptive qualitative research method, namely literature study or literature review. Researchers collect data and information from journals, books and other scientific works in accordance with the discussion in this article. Through this article, it is hoped that it can encourage all aspects of the implementation of education in Indonesia towards better quality so that education graduates can respond to the needs and challenges of the times.